Hadith #2295 - Sunan Abi Dawud - Ja'far bin Brqan جعفر بن برقان; Maymun bin Mahran ميمون بن مهران; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Yahya ibn Sa’id ibn al-‘As divorced the daughter of ‘Abd al-Rahman ibn al-Hakam absolutely. ‘Abd al-Rahman shifted her (from there). Aisha sent a message to Marwan ibn al-Hakam who was the governor of Medina, and said to him: Fear Allah, and return the woman to her home. Marwan said (according to Sulayman’s version): ‘Abd al-Rahman forced me. Marwan said (according to the version of al-Qasim): Did not the case of Fatimah daughter of Qays reach you? Aisha replied: There would be no ha
Grade: Sahih

Hadith #3409 - Sunan Abi Dawud - Ayoub bin Muhammad al-Wazan أيوب بن محمد بن زياد الوزان; ibn Abbas; Ja'far bin Brqan جعفر بن برقان; Maqsim bin Bajra مقسم بن بجرة; Maymun bin Mahran ميمون بن مهران; Umar bin Ayoub al-Bdy عمر بن أيوب العبدي (Sunan Abi Dawud)
The Prophet (ﷺ) handed over the Jews of Khaibar the palm trees and the land of Khaibar on condition that they should employ what belonged to them in working on them, and that he should have half of the fruits.
Grade: Sahih

Hadith #3802 - Sunan Abi Dawud - ibn Abbas; Ja'far bin Iyas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Maymun bin Mahran ميمون بن مهران; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited eating fanged beasts of prey.
Grade: Sahih

Hadith #3804 - Sunan Abi Dawud - ibn Abbas; Maymun bin Mahran ميمون بن مهران; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Beware, the fanged beast of prey is not lawful, nor the domestic asses, nor the find from the property of a man with whom treaty has been concluded, except that he did not need it. If anyone is a guest of people who provide no hospitality for him, he is entitled to take from them the equivalent of the hospitality due to him.
Grade: Sahih